Pseudogenes Provide Evolutionary Evidence for the Competitive Endogenous RNA Hypothesis - Mc Lysaght, Aoife (My University, 2018)
The competitive endogenous RNA (ceRNA) hypothesis is an attractively simple model to explain the biological role of many putatively functionless noncoding RNAs. Under this model, there exist transcripts in the cell whose role is to titrate out microRNAs such that the expression level of another target sequence is altered. That it is logistically possible for expression of one microRNA recognition element (MRE)-containing transcript to affect another is seen in the multiple examples of pathogenic effects of inappropriate expression of MRE-containing RNAs. However, the role, if any, of ceRNAs in normal biological processes and at physiological levels is disputed. By comparison of parent genes and pseudogenes we show, both for a specific example and genome-wide, that the pseudo-30 untranslated regions (30UTRs) of expressed pseudogenes are frequently retained and are under selective constraint in mammalian genomes. We found that the pseudo-30UTR of BRAFP1, a previously described oncogenic ceRNA, has reduced substitutions relative to its pseudo-coding sequence, and we show sequence constraint on MREs shared between the parent gene, BRAF, and the pseudogene. Investigation of RNA-seq data reveals expression of BRAFP1 in normal somatic tissues in human and in other primates, consistent with biological ceRNA functionality of this pseudogene in nonpathogenic cellular contexts. Furthermore, we find that on a genome-wide scale pseudo-30UTRs of mammalian pseudogenes (n ¼ 1,629) are under stronger selective constraint than their pseudo-coding sequence counterparts, and are more often retained and expressed. Our results suggest that many human pseudogenes, often considered nonfunctional, may have an evolutionarily constrained role, consistent with the ceRNA hypothesis.
PUBLISHED
Keywords: competitive endogenous RNA (ceRNA); microRNA recognition element (MRE); pseudogenes; ceRNA; Pseudogenes; BRAF; Evolutionary rates